Addressing Slow Charging Concerns in Current Electric Vehicles: A Comprehensive Analysis - Saji, Ashish; Ansurkar, Gauri (Science and Technology - Recent Updates and Future Prospects Vol. 1, 2024)
This study investigates the challenges and potential solutions regarding the adoption of electric vehicles (EVs) amidst increasing pollution and climate change concerns. Through a comprehensive review of existing literature and analysis of survey data from 200 participants, this research sheds light on the factors influencing individuals' readiness to switch to EVs. Results indicate that while there is a growing trend towards EVs globally, significant barriers such as slow charging times hinder widespread adoption. The study explores the impact of battery size, charging infrastructure, and environmental factors on charging speed, proposing innovative solutions such as self-heating batteries and advanced charging technologies to overcome these challenges. By providing insights into the current state of EV adoption and suggesting strategies for improvement, this research contributes to the ongoing discourse on sustainable transportation and environmental conservation.